Gold–Ceria SBA-15-Supported Catalyst for CO Preferential Oxidation: Surface and Reactivity Studies - Álvaro Reyes-Carmona; Aldo Talon; Elisa Moretti; Maurizio Lenarda; Antonio Jiménez-López; Enrique Rodríguez-Castellón (Adsorption Science & Technology, 2012)
In this article, the preparation and application of gold and cerium catalysts supported on zirconium-doped mesoporous silica SBA-15 was studied. These materials have been prepared by two different methods and characterized to investigate their textural properties, dispersion of the active phases and oxidation states. Both materials exhibit a marked catalytic activity. The size of the gold nanoparticles is directly related to the CO conversion rate and to the selectivity towards CO 2 exhibiting a strong temperature dependence. An X-ray photoelectron spectroscopic study of the composition and chemical state of the nanoparticles indicates the presence of Au in a metallic state. Transmission electron microscopic micrographs indicate that the best catalyst shows a higher dispersion of Au in spite of its lower gold surface content.